PELATIHAN PROGRAM HACCP BAGI PENGUSAHA UMKM DI WILAYAH TANGERANG - Prawira, Oqke; Armielia, Adestya Ayu; Pradiati, Savira (Universitas Pelita Harapan, 2023)
When MSMEs become a sector that is badly affected by the Covid-19 pandemic, MSME entrepreneurs in the culinary field need a strategy to rise up, and in this case is the implementation of food safety and the implementation of stricter health protocols, so that consumers can feel safe when consuming processed food and beverage products. Monitoring and evaluation of hygiene and sanitation in the processing and packaging process are needed to break the chain of transmission and contamination of both viruses and bacteria in food to consumers. Improving the quality of products from MSME entrepreneurs in culinary sectors includes the implementation of stricter standards and regulations. HACCP is a science-based systematic method that identifies specific hazard risks and their control measures to ensure the safety of manufactured food products. HACCP focuses on the prevention so this method can assist the user in designing processing equipment and procedures. HACCP training for food and beverage MSME entrepreneurs in Tangerang, especially in the Gading Serpong area, is expected to be a solution to the problems of MSME entrepreneurs to gain consumer trust by processing food and beverage products that are safe, healthy, and hygienic for their F&B businesses in accordance with proper health protocols.